Vocabulary of Ponape dialect - Doane, Edward Topping, 1820-1890.
Vocabulary in English with equivalent words written in the Ponape dialect used in Ponape, Micronesia, compiled by Doane.
Collection material in English, with Ponape.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Pohnpeian language; Caroline Islands -- Languages